ANGPTL3, ANGPTL4, APOA5, APOB, APOC2, APOC3, LDLR, PCSK9, LPL gene variants and coronary artery disease risk - A. N. Meshkov; A. V. Kiseleva; A. I. Ershova; E. A. Sotnikova; S. A. Smetnev; A. S. Limonova; A. A. Zharikova; M. Zaychenoka; V. E. Ramensky; O. M. Drapkina (Российский кардиологический журнал, 2022)
Aim. To study the contribution of rare and low-frequency variants of ANGPTL3, ANGPTL4, APOA5, APOB, APOC2, APOC3, LDLR, PCSK9, LPL genes in assessing the risk of coronary artery disease (CAD) in a cohort of Russian patients with various cardiovascular risks.Material and methods. The study was conducted on a sample of participants in cohort and epidemiological studies (n=2405). Targeted enrichment of coding sequences and exon-intron regions of nine genes (ANGPTL3, ANGPTL4, APOA5, APOB, APOC2, APOC3, LDLR, PCSK9, LPL) was performed. Genetic diagnostics was carried out by next generation sequencing.Results. CAD was confirmed in 267 patients (11%). After genetic diagnosis, all patients were divided into three following groups: individuals with previously described genetic variants associated with elevated levels of low-density lipoprotein cholesterol (LDL-C) and/or triglycerides (TGs); individuals with genetic variants associated with reduced levels of LDL-C and/or TGs; individuals without genetic variants associated with LDL-C and/or TG levels, or with two or more variants with opposite effects on LDL-C and/or TG levels. Kaplan-Meier method revealed that the groups significantly differ in cumulative risk of CAD (p<0,001 for the log-rank test), the maximum risk was in group 1, and the minimum risk in group 2. When conducting the Cox regression, we found that in persons from group 1, the hazard ratio (HR) for CAD is 2,63 times higher (HR =2,63, 95% confidence interval (CI), 1,6-4,34; p><0,001), and in persons from group 2 lower by 1,88 times (HR =0,53, 95% CI, 0,3-0,98; p=0,042) compared with persons from group 3, adjusted for other CAD risk factors: sex, age, smoking, LDL-C and hypertension. Conclusion. Genetic testing in young patients makes it possible to identify individuals with an increased genetic risk of CAD and to focus preventive and therapeutic measures primarily for this category of patients. Keywords: coronary artery disease, cardiovascular diseases, low-density lipoprotein cholesterol, genetic testing. Relationships and Activities: none. 1National Medical Research Center for Therapy and Preventive Medicine, Moscow; 2Pirogov Russian National Research Medical University, Moscow; 3E. I. Chazov National Medical Research Center of Cardiology, Moscow; 4Lomonosov Moscow State University, Moscow; 5Moscow Institute of Physics and Technology, Dolgoprudny, Russia.><0,001 for the log-rank test), the maximum risk was in group 1, and the minimum risk in group 2. When conducting the Cox regression, we found that in persons from group 1, the hazard ratio (HR) for CAD is 2,63 times higher (HR =2,63, 95% confidence interval (CI), 1,6-4,34; p<0,001), and in persons from group 2 lower by 1,88 times (HR =0,53, 95% CI, 0,3-0,98; p=0,042) compared with persons from group 3, adjusted for other CAD risk factors: sex, age, smoking, LDL-C and hypertension.Conclusion. Genetic testing in young patients makes it possible to identify individuals with an increased genetic risk of CAD and to focus preventive and therapeutic measures primarily for this category of patients.